2022
DOI: 10.1039/d2ra00602b
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/(Ta2O5–SnO2) hybrid nanocomposite for efficient room temperature CO gas sensing

Abstract: Room temperature CO sensing using a hybrid (Ta2O5–SnO2) : PANI composite material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The presence of oxygen vacancies (V O •• ) is consistent with the substoichiometric nature of the oxide, as mentioned above. Similarly, composites of Ta 2 O 5 –SnO 2 –PANI were reported to contain oxygen vacancies of high concentration along with N cation radicals, which are ascribed to the formation of the hybrid structures . The proportion of the higher BE components is larger in the region closer to the Si substrate, which is consistent with the gradual blue shift of the In 3d peaks (Figure S4).…”
Section: Resultsmentioning
confidence: 90%
“…The presence of oxygen vacancies (V O •• ) is consistent with the substoichiometric nature of the oxide, as mentioned above. Similarly, composites of Ta 2 O 5 –SnO 2 –PANI were reported to contain oxygen vacancies of high concentration along with N cation radicals, which are ascribed to the formation of the hybrid structures . The proportion of the higher BE components is larger in the region closer to the Si substrate, which is consistent with the gradual blue shift of the In 3d peaks (Figure S4).…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the sensor showed high selectivity, and excellent repeatability -superior properties that can be attributed to the meso-macropores sensor structure, recognition function of amino groups, and formation of P-N heterojunction between BP and PEI. Ta 2 O 5 -SnO 2 -PANI hybrid composite for efficient sensing of CO at room temperature at very low concentration, have been reported by Aranthady et al, 118 The hybrid material exhibited superior CO sensing performance with high sensitivity, low operating temperature, fast response and fast recovery compared to the individual components. The enhanced sensing ability of the hybrid material has been attributed to the synergistic properties such as conductivity of PANI, improved oxygen vacancies and the heterostructure formed between the PANI and the (Ta 2 O 5 -SnO 2 ) composite (Table 5).…”
Section: Polymer-based Nano Materialsmentioning
confidence: 85%
“…SnO 2 , an n-type wide band gap semiconductor metal oxide with high mobility of electrons and high chemical and thermal stability, is considered a promising candidate for the fabrication of PANI composite sensors in many research studies. [132][133][134] To further optimize the sensing performance, some metal particles and carbon nanomaterials are also doped into PANI/ SnO 2 sensing composites. [135][136][137] Aliha et al 138 reported the SnO 2 / PANI nanocomposite material for selective detection of ammonia at room temperature.…”
Section: Pani-metal Oxide Compositesmentioning
confidence: 99%